DEVELOPMENT OF RESEARCH FRAMEWORK FOR PBL PROBLEM SCENARIO USING LINEAR & NON-LINEAR MULTIMEDIA - Wan Mohd Puzi, W. N.; Hussin, B.; Shahbodin, F. (2010)
Problem Based Learning (PBL) is an instructional approach to provide student with knowledge suitable for problem solving. To support the research, PBLStat courseware is developed based on the PBL approach. In PBL approach, problem scenario is first presented during the learning process. Problem scenario helps to maintain student interest in course so it is important to create a good problem that can cause students‘ inquiry and drive students to solve the problems. The purpose of this paper is to highlight the development of research framework for PBL problem scenario presentation. Problem scenario can be presented using linear and non-linear multimedia categories. The framework of study contains the description of research control modes, content and output. The control modes of the research are consisting of two independent variables which are linear problem scenario and non-linear problem scenario. Content is the phase of courseware‘s development. The ADDIE model is used to complete the development of courseware. Finally is the research output, this is to evaluate student‘s preferences and performances based on the problem scenario categorization. There are four research instrument tools has been created to answer the research question which are questionnaire, observation, interview and PBLStat.